LONO-QCL (High reliability LOw-NOise Quantum Cascade Lasers for Earth observation) - (:unkn) unknown (My University, 2025)
The quantum cascade laser (QCL) is a relatively young technology for coherent light emission in the important mid-infrared spectral region that contains the "fingerprint" absorption spectrum of most molecules. Tremendous progress and improvements have been achieved in their general properties (e.g., singlemode emission, room temperature continuous wave operation, high output power, large spectral coverage) since their invention just 20 years ago. This has made QCLs the most versatile mid-infrared laser source, widely used in numerous applications in high-resolution spectroscopy and trace gas sensing, e.g, for Earth and atmosphere monitoring. However, the noise characteristics and spectral purity of these lasers have been much less investigated so far. Narrow-linewidth lasers in the mid-infrared are important for many emerging applications in metrology, free-space communications and high precision spectroscopy. The goal of the project was to better understand 1/f frequency noise processes in QCLs and to identify and study parameters that play a central role in the noise generation. This is an important step for a future use of this technology in novel space applications for Earth observation or for the study of the atmosphere of other planets, whereas QCLs have only been deployed in balloon- and air-borne instruments to-date, but have never been flown to space. Switzerland will certainly have a major role to play in such an adventure owing to its strong position in the field of QCLs, both at research and industrial levels.
Keywords: Lasers à cascade quantique; largeur de raie; bruit de fréquence; stabilisation